Efektivitas Pengelolaan Badan Usaha Milik Desa (BUMDes) Dalam Meningkatkan Pendapatan Asli Desa (PADes) Di Desa Sukanagara, Kecamatan Lakbok, Kabupaten Ciamis - Roufurrohim Roufurrohim; Irma Bastaman (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
The problem of this research is that BUMDes management has not been carried out optimally. The presence of BUMDes has not increased Village Original Income (PADes) for community welfare. This research uses a descriptive method with a qualitative approach. Data collection techniques through observation, interviews, documentation and literature study. Data analysis techniques namely data collection, data reduction, data presentation and drawing conclusions. The results of the study show that the management has been carried out quite well, out of the five management principles only three have been fulfilled, two principles have not been fulfilled. The results of the study also show that: socialization has been carried out but has not been conveyed to the whole community, many people do not know about BUMDes programs and business units. Community interest and participation is still lacking, lack of community involvement in capital and management. BUMDes management has also not created jobs. Management is not timely in achieving BUMDes goals. The results of BUMDes management have not increased the economy and social welfare as a form of real change. The benefits of BUMDes are only limited to serving business units.